2022
DOI: 10.1039/d2ce00765g
|View full text |Cite
|
Sign up to set email alerts
|

Chain dimension and crystallization temperature affect the III transition of isotactic polybutene-1

Abstract: Isotactic polybutene-1 (iPB-1) usually crystallizes into Form II from melt first and then spontaneously transforms into Form I that with outstanding properties. It is still open to the mechanism of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…It was found that the amorphous regions play an important role in the transition of iPB-1, which has been confirmed by recent observations when modifying the amorphous regions in iPB-1 blends. 35 Typically, the entropy of liquids falls faster than that of crystals with decreasing temperature. Therefore, the entropy of the amorphous regions decreases faster than that of the crystalline regions as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the amorphous regions play an important role in the transition of iPB-1, which has been confirmed by recent observations when modifying the amorphous regions in iPB-1 blends. 35 Typically, the entropy of liquids falls faster than that of crystals with decreasing temperature. Therefore, the entropy of the amorphous regions decreases faster than that of the crystalline regions as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Qiao et al 21 reported that the transition rate of high molecular weight samples is positively correlated with the crystallization temperature, while that of low molecular weight samples is negatively correlated with the temperature. They considered that this correlation depends on the ability to generate entanglements for transferring internal stresses caused by differences in the coefficients of thermal expansion between the crystalline and amorphous regions during cooling and thereby inducing nucleation of form I. Cui et al 22 found that the II–I transition of the high molecular weight samples exhibits more sensitivity to conditions for the crystallization of form II than that of the low molecular weight samples. They proposed that the phenomenon could be attributed to the role of the amorphous regions in the transition.…”
Section: Introductionmentioning
confidence: 99%
“…38 Minor form I had been reported to directly crystallize from the amorphous phase of bulk iPB-1, 39 particularly for iPB-1 with a molecular weight of M w = 259.2 × 10 4 g mol −1 . 40 Furthermore, form II can be stabilized by random copolymerization of butene-1 and 4-methyl-1-pentene 41 or under confinement of nanoporous alumina. 42 The role of iPB-1 amorphous phase rather than the crystalline phase of form II crystals tends to be crucial during the II-I transition.…”
Section: Introductionmentioning
confidence: 99%
“…41 A slower form II to form I transition rate was observed with increasing molecular weight by Cui, which is attributed to the bigger size of the amorphous region in higher molecular weight compounds. 42 Pan et al reported that the entanglement affected the crystallization of form II and the transition of iPB-1 obtained from solution. 28,43,44 The aforementioned results present challenges to understanding the form II to form I transition in iPB-1 based on the widely accepted transition mechanism.…”
Section: Introductionmentioning
confidence: 99%